Ecological and economical alternative for Coffea arabica L. seedling obtainment - Moisés M., Luis Gustavo; Tamayo A., Yonger; Barraza A., Fernando Vicente (Revista de Ciencias Agrícolas, 2015)
The experiment was made in the Limonar located in the El Salvador municipality, with the objective to evaluate the behavior of the coffee seedling Coffea arabica L. with two stocks of arbuscular mycorrizal fungi (HMA) in the coffee productive system of Limonar. The system of sowing in breeding grounds in polyethylene stock market was used with a total of 360 plants, from them 120 were taken to be evaluated. It was Completely used a design randomized with three treatments and retorts four, resultants of the inoculation of the seeds of coffee plant with two stump of HMA Rhizophagus intraradices and Glomus cubense and a control without inoculation, the same one mounted on a substrate conformed by a relation soil organic matter (Bovine) 5:1. Morphologic variables like pairs of leaves, area to foliar (cm2), height of the plants, length by the root, dry matter (g) and the Index of efficiency were evaluated (IE). An analysis of variance of simple classification was made, the results threw that the inoculation of the arbuscular mycorrizal fungi increased all the indicators studied for the coffee seedling in the conditions of study, presenting environmental benefits and ecological.